A novel lncRNA BADLNCR1 inhibits bovine adipogenesis by repressing GLRX5 expression. Issue 13 (25th May 2020) - Cai, Hanfang; Li, Mingxun; Jian, Wang; Song, Chengchuang; Huang, Yongzhen; Lan, Xianyong; Lei, Chuzhao; Chen, Hong
Abstract: Adipogenesis is a complex cellular process, which needs a series of molecular events, including long non‐coding RNA (lncRNA). In the present study, a novel lncRNA named BADLNCR1 was identified as a regulator during bovine adipocyte differentiation, which plays an inhibitory role in lipid droplet formation and adipogenic marker gene expression. CHIPR‐seq data demonstrated a potential competitive binding motif between BADLNCR1 and sterol regulatory element‐binding proteins 1 and 2 (SREBP1/2). Dual‐luciferase reporter assay indicated target relationship between KLF2 and BADLNCR1 . Moreover, after the induction of KLF2, the expression of adipogenic gene reduced, while the expression of BADLNCR1 increased. Real‐time quantitative PCR (qPCR) showed that BADLNCR1 negatively regulated mRNA expression of GLRX5 gene, a stimulator of genes that promoted formation of lipid droplets and expression of adipogenic genes. GLRX5 could partially reverse the effect of BADLNCR1 in bovine adipocyte differentiation. Dual‐luciferase reporter assay stated that BADLNCR1 significantly reduced the enhancement of C/EBPα on promoter activity of GLRX5 gene. Furthermore, CHIP‐PCR and CHIRP‐PCR confirmed the suppressing effect of BADLNCR1 on binding of C/EBPα to GLRX5 promoter. Collectively, this study revealed the molecular mechanisms underlying the negative regulation of BADLNCR1 in bovine adipogenic differentiation.